Bâtir des ponts : Perceptions et réalités à propos des communautés d'expression anglaise du Québec et leur relation avec le francais au Québec et le bilinguisme au Canada - Canada. Office of the Commissioner of Official Languages (2024)
Le Commissariat aux langues officielles (le Commissariat) a observé qu’au cours des dernières années, les communautés d’expression anglaise du Québec (CEAQ) se sont souvent retrouvées au coeur du discours et des débats publics dans la province. Des données tirées de sondages et du recensement révèlent qu’en général, les communautés anglophones de la province sont en grande partie bilingues et qu’elles valorisent la dualité linguistique du Canada, y compris la langue française. L’on ignore, toutefois, dans quelle mesure la population générale est consciente de ces faits à propos des CEAQ et le Commissariat souhaitait vérifier l’hypothèse selon laquelle des mythes problématiques persistent. Dans ce contexte, et compte tenu de la modernisation de la Loi sur les langues officielles par le gouvernement fédéral en 2023, qui reconnaît la nécessité de « favoriser l’existence d’un foyer francophone majoritaire dans un Québec où l’avenir du français est assuré », ce projet de recherche est l’occasion de faire la lumière sur la relation que les communautés d’expression anglaise du Québec entretiennent avec la langue française dans la province et le bilinguisme officiel au Canada dans son ensemble. Ce projet permet aussi d’explorer la possibilité que les membres de la minorité anglophone du Québec soient considérés comme des bâtisseurs de ponts, ou même comme des alliés de la promotion du français au Canada, en vue de développer un discours plus constructif qui illustre clairement leurs contributions et, au bout du compte, vient déconstruire certaines perceptions erronées.
Keywords: Official Language Minority Community (OLMC)

Building Bridges : Perceptions and Realities About the English-speaking Communities of Quebec and their Relationship with French in Quebec and Bilingualism in Canada - Canada. Office of the Commissioner of Official Languages (2024)
The Office of the Commissioner of Official Languages (the Office of the Commissioner) has observed that, in recent years, the English-speaking communities of Quebec (ESCQ) have been the focus of much public discourse and debate in the province. Survey and census data indicate that, overall, the ESCQ are highly bilingual and value Canada’s broader linguistic duality, including the French language. The extent to which the general population is aware of these facets of the ESCQ is not clear, however, and the Office of the Commissioner wished to test the hypothesis that problematic myths may persist. In light of this context and with the modernization of the Official Languages Act by the federal government in 2023, which recognizes the need to “advance the existence of a majority-French society in a Quebec where the future of French is assured,” this research project is an opportunity to shed light on the relationship that the ESCQ have with the French language in Quebec and official bilingualism in Canada as a whole. This is also an opportunity to explore how Quebec’s English-speaking minority can be considered as bridge-builders or even as a potential ally of the promotion of French in Canada as a whole, with a view to developing a more constructive discourse that better acknowledges their contributions and, ultimately, deconstructs certain misperceptions.
Keywords: Official Language Minority Community (OLMC)

QFHSA Board of Directors Shocked at CAQ Attack on McGill, Concordia, and Bishop's - Quebec Federation of Home and School Associations (QFHSA) (2023)

Committee Adopts Series of Surprise Changes Regarding Bilingualism in Quebec Judicial Appointments - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Policy Matters Blog #23 - Bill 96

La Commission adopte une série de changements surprenants en matière de bilinguisme concernant les nominations à la magistrature du Québec - Quebec Community Groups Network (QCGN) (2022)
Parallel title: Question de politique - Blogue no. 23 (Projet de loi 96)

Nos pionniers locaux! : Un balado sur la contribution et la collaboration entre les francophones et les anglophones à la société québécoise en Outaouais d’hier à aujourd’hui. - Nivischiuk, Jeanne (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

French-language Support for Québec's English-speaking Professionals - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
French-language barriers can be a challenge for professionals who are English speakers and must practice their profession in accordance with French-language policies. Despite high levels of English-French bilingualism among Québec’s English speakers, French remains a challenge for some who require additional profession-specific French-language training. Not only is French-language proficiency a requirement for membership in Québec’s professional orders, but professionals who do not meet language criteria must also pass a French-language competency exam administered by the Office québécois de la langue française (OQLF). Additionally, professional orders can mandate all their members to take French-language professional competency exams throughout their careers.

Soutien en langue française pour les professionnelles et professionnels d'expression anglaise au Québec - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
La langue française peut représenter un obstacle pour les professionnelles et professionnels d’expression anglaise qui doivent exercer leur profession en respectant les politiques linguistiques en place. Malgré un haut niveau de bilinguisme parmi les Québécois·e·s d’expression anglaise, le français demeure une embuche pour certain∙e∙s. Ces personnes professionnelles bénéficieraient de formation linguistique additionnelle en lien avec leur métier. Non seulement la maîtrise du français est un prérequis pour se joindre aux ordres professionnels québécois, mais, dans certains cas, les personnes qui ne satisfont pas aux critères linguistiques doivent aussi passer un examen de français de l’Office québécois de la langue française (OQLF). En outre, les ordres professionnels peuvent demander à leurs membres de se soumettre, durant leur carrière, à des examens de compétences linguistiques en français.

Bill 96 & Employment of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
On May 24, 2022, Québec’s National Assembly passed Bill 96, An Act Respecting French, the Official and Common Language of Québec. The bill, which presents significant modifications to The Charter of the French Language (Bill 101), as well as other existing legislation, was passed more than a year after it was introduced. On June 1, 2022, Bill 96 received royal assent and some of its clauses came into effect immediately. Other clauses of the bill will come into effect at later dates.

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Programmes de francisation de la main-d'oeuvre au Québec : Évaluation des programmes de francisation de la main-d'oeuvre québécoise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport se penche sur l’état des programmes de francisation pour la main-d’oeuvre (PFMO) au Québec. Les PFMO sont des cours de français spécifiquement conçus pour accroître l’intégration des apprenantes et apprenants de langues sur le marché du travail en étant axés sur le vocabulaire et les compétences linguistiques qui contribuent à leur employabilité. Dans ce rapport nous avons recensé les PFMO offerts aux apprenantes et apprenants de langue française, et relevé les besoins clés, les lacunes et les possibilités d’amélioration au sein de l’écosystème.

Hats and High Tea : Local Collector to Share "Mobile Museum" in Bilingual Talk Highlighting the History of Fashion from 1940-1965, Followed by a Traditional English-style High Tea - Centre for Access to Services in English (CASE) (2021)

Resolution 2021-01 : Free French Instruction Services for all Who Request Them - Quebec Federation of Home and School Associations (QFHSA) (2021)

Ce que la population canadienne pense de l'apprentissage du français et de l'anglais - Canada. Office of the Commissioner of Official Languages (2021)

Ce que la population canadienne pense du bilinguisme officiel et de la Loi sur les langues officilles - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Learning English and French - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Official Bilingualism and the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2021)

Enjeux de l'éducation bilingue dans les écoles anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Parallel title: Résumé de recherche en éducation no 6
Keywords: Official Language Minority Community (OLMC)

Issues of Bilingual Education in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The percentage of Quebec’s population with French-English bilingual skills has steadily increased over the past decades, and this is the case for all Quebecers, regardless of language background (Turcotte, 2019). Quebec Anglophone youth, however, are the most bilingual, and become bilingual at a younger age than Francophone or Allophone youth. The explanation is simple: Quebec’s English-speaking parents have been able to rely on schools to develop their children’s bilingual skills, thanks to French immersion and other enriched French-secondlanguage programs (Lamarre, 1997, 2007, 2012; Magnan et al., 2018), and in some cases by crossing over to the French sector (Laperrière & Lamarre, 2006).
Parallel title: Education Research Brief no. 6
Keywords: Official Language Minority Community (OLMC)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)